Properties of Fly Ash-Slag-Based Geopolymer Concrete with Low Molarity Sodium Hydroxide - Ernawati Sri Sunarsih; Sholihin As'ad; Abdul Rahman Mohd Sam; Stefanus Adi Kristiawan (Salehan Institute of Higher Education, 2023)
Most geopolymer concrete is produced using low-calcium fly ash and cured at high drying temperatures. Additionally, the activator is prepared with a sodium hydroxide (SH) solution of high molarity. This research proposes using a low molarity SH solution to produce fly ash-slag-based geopolymer concrete cured at room temperature. The properties to be investigated include workability, water absorption, and compressive strength. The influence of mixture composition, i.e., slag content, sodium silicate to sodium hydroxide (SS/SH) ratio, and alkaline activator to binder (Al/Bi) ratio on those properties is of interest. The slag substituted fly ash at 10, 20, 30, 40, and 50% replacement levels. The SS/SH ratio is 1.0, 1.5, and 2.0, with the SH molarity determined at 2M. The Al/Bi ratio is 0.40, 0.45, and 0.50. The results show that a higher percentage of slag reduces slump and water absorption but increases the compressive strength of the geopolymer concrete. The mixtures suitable for use are at the percentages of slag 20, 30, and 40%. An increase in the SS/SH ratio decreases the slump and water absorption. Geopolymer concrete with an SS/SH ratio of 1.5 gives maximum compressive strength compared to the other ratios. Increasing the ratio of Al/Bi increases the workability of geopolymer concrete. At an Al/Bi ratio of 0.45, the compressive strength is maximum and the water absorption is minimum. The recommended mix design in terms of workability, water absorption, and compressive strength of geopolymer concrete is a mixture with slag contents of 20, 30, and 40%, a SS/SH ratio of 1.0 and 1.5, and an Al/Bi ratio of 0.45 and 0.50. Doi: 10.28991/CEJ-2023-09-02-010 Full Text: PDF